Amyotrophic Lateral Sclerosis: A Neurodegenerative Motor Neuron Disease With Ocular Involvement - Rojas, Pilar; Ramírez, Ana I.; Fernández-Albarral, José A.; López-Cuenca, Inés; Salobrar-García, Elena; Cadena, Manuel; Elvira-Hurtado, Lorena; Salazar, Juan J.; de Hoz, Rosa; Ramírez, José M. (Frontiers in Neuroscience, 2020)
Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease that causes degeneration of the lower and upper motor neurons and is the most prevalent motor neuron disease. This disease is characterized by muscle weakness, stiffness, and hyperreflexia. Patients survive for a short period from the onset of the disease. Most cases are sporadic, with only 10% of the cases being genetic. Many genes are now known to be involved in familial ALS cases, including some of the sporadic cases. It has also been observed that, in addition to genetic factors, there are numerous molecular mechanisms involved in these pathologies, such as excitotoxicity, mitochondrial disorders, alterations in axonal transport, oxidative stress, accumulation of misfolded proteins, and neuroinflammation. This pathology affects the motor neurons, the spinal cord, the cerebellum, and the brain, but recently, it has been shown that it also affects the visual system. This impact occurs not only at the level of the oculomotor system but also at the retinal level, which is why the retina is being proposed as a possible biomarker of this pathology. The current review discusses the main aspects mentioned above related to ALS, such as the main genes involved, the most important molecular mechanisms that affect this pathology, its ocular involvement, and the possible usefulness of the retina as a biomarker.